Computational Simulation of Laminar Heat Convection of Nanofluids in a Circular Tube and Squared Duct [Simulación Computacional de Convección de Calor Laminar de Nanofluidos en Tubo Circular y Ducto Cuadrado] - Acevedo-Cabello, J; Chen, D; Vasco-Calle, D (Universidad Nacional de Colombia, 2016)
Nanofluids are colloidal suspensions of nanometer-sized particles (metals, metallic oxides or carbon nanotubes) in a base fluid (polar or non-polar). Nanofluids have interesting properties that make them useful especially in the design of compact heat transfer equipment. Laminar convective heat transfer of nanofluids (water, Al2O3) in a square and circular ducts has been studied numerically using the software ANSYS/FLUENT 12.1. Results for the Nusselt number, skin coefficient friction, temperature and velocity profiles are presented for four nanoparticle volume fractions (φ = 0 − 20%) and Reynolds numbers (Re = 800, 1300 and 2000). For the studied Re numbers, Nu is decreased by 12% and 10%, when φ is increased from 0% to 10% and from 10% to 20%, respectively. Regard to the skin friction factor, the obtained value is increased around a 30% when ϕ is increased 10%. © The author; licensee Universidad Nacional de Colombia.